2020
DOI: 10.21203/rs.2.24171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of chitosan-propolis nanoparticle against Enterococcus faecalis biofilms in the root canal

Abstract: Background To determine the antibacterial effect of chitosan-propolis nanoparticle (CPN) as an intracanal medicament against Enterococcus faecalis biofilm in root canal. Methods 240 extracted human teeth were sectioned to obtain 6mm of the middle third of the root. The root canal was enlarged to an internal diameter of 0.9mm. The specimens were inoculated with E. faecalis for 21 days. Following this, specimens were randomly divided into eight groups ( n=30 ) according to the intracanal medicament placed: group… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…These results are in accordance with Parolia et al (2020) study, which found that chitosan was less effective than calcium hydroxide and propolis against E. faecalis after 1 week of dressing application.…”
Section: F I G U R Esupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in accordance with Parolia et al (2020) study, which found that chitosan was less effective than calcium hydroxide and propolis against E. faecalis after 1 week of dressing application.…”
Section: F I G U R Esupporting
confidence: 92%
“…The concentration of chitosan in Parolias' study was 0.2%, which was conducted on permanent teeth, E. faecalis were incubated for 21 days, and the bacterial suspension was used at (1.5 × 10 8 CFUs/ mL), yet the results of both studies were similar, which can lead to conclude that the effect of calcium hydroxide is higher in comparison to chitosan, even when the concentration of the last one was increased here (Abhishek Parolia et al, 2020).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations